Relationship of serum vitamin D with hepatic fibrosis in patients with chronic hepatitis C - Behera, Manas Kumar; Swain, Surendra Nath; Abhilash, V. B.; Shukla, Sunit Kumar; Dixit, Vinod Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Serum vitamin D concentration is proposed to have an important role on outcome in patients with chronic hepatitis C virus (HCV) infection. A few studies have shown an inverse association of vitamin D level with stage of fibrosis. The aim of the present study was to verify whether serum vitamin D level is an independent predictor of significant hepatic fibrosis. Methods: Seventy-two treatment naive chronic HCV subjects and 40 healthy age and sex matched controls were included in the study. A serum vitamin D level was assessed in both HCV subjects and controls, and liver biopsy was performed in all HCV subjects to assess for stage of fibrosis. Results: Serum vitamin D levels were significantly lower HCV patients in comparison to age and sex matched controls (18.04±6.92 versus 21.53±8.2, p<0.01). Most common genotype in HCV patients was genotype 3 (62.5%) and blood transfusion was the most common mode of transmission (28%) followed by intravenous drug user (IVDU) (17%). The HCV patients with vitamin D level <20 ng/ml had higher metavir score as compared to vitamin D≥20 ng/ml (1.67±0.66 versus 2.5±0.67, p<0.001). Both univariate and multivariate analysis performed using logistic regression revealed that vitamin D<20 ng/dl is a significant negative predictor of liver fibrosis (p<0.05). Conclusions: Chronic HCV patients had significantly lower vitamin D levels as compared to healthy controls. Serum vitamin D was a negative predictor of stage of fibrosis in patients with chronic hepatitis C.